Can AI Systems Be HIPAA Compliant? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2019)
The integration of Artificial Intelligence (AI) into healthcare offers revolutionary advancements in diagnostics, treatment, and operational efficiency. AI p...
Keywords: Healthcare Data Privacy and Security; Systems; HIPAA; Compliant; Artificial Intelligence; Machine Learning; Healthcare